Equilibrium in Stable Markets - Ohlson, James A. (Journal of Political Economy, 1977)
E. Fama (1971) has shown that the classical, two-period, two-parameter capital asset pricing model can be generalized to the case of symmetric stable distributions. Fama develops his results using a one-factor ("market-model") distribution of returns. The present research shows that the same equilibrium results hold for all stable distributions of returns which allow for a concave and differentiable objective function; there is no need to assume symmetry or any other restrictions on the return structure. Furthermore, derivations are straightforward in that they rely only on elementary properties of homogeneous functions.